Pemanfaatan Personal Health Record Dalam Mengontrol Kesehatan Individu (Literature Riview) - Regina Yulianti T. S; Laela Indawati; Lily Widjaja; Daniel Happy Putra (Jurnal Medika Nusantara, 2024)
Individuals are authorized to access, maintain, and share their Personal Health Record (PHR), which is an electronic application, in a private, secure, and confidential setting. Using PHR will facilitate patient-provider communication. PHR has two-way communication that allows patients and providers to communicate with each other. The main effect of using PHR is that patients will be involved and take an active role in their health and disease prevention. The act of recording health information in PHR will increase patient awareness, such as weight, diet and glucose, and other health checks. Through PHR which stores health information, and consultations, patients feel safe knowing their health. The purpose of this writing is to determine the Utilization of Personal Health Record in controlling individual health. This study uses the Literature Review method. The results of this study are seen from the utilization and features of the Personal Health Record. Utilization of the Personal Health Record in controlling individual health can assist patients in accessing patient personal health information such as knowing blood sugar, blood pressure, laboratory results, and so on. The features used in the PHR have a main menu including health records, medical records, test results, medication reminders, health contacts, and education.